Review on Double Acting Tanker Ship in Ice Mode - Afrizal, Efi; Koto, J.; A, Wahid M.; Siow, C. L. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Podded propulsion system has been utilized to make revolutionary in the integrated ship propulsion and steering system due to diesel-electric and combining pod and rudder in the compact body. This paper would review utilization of podded propulsion system on the Double Acting Tanker (DAT) ship in ice mode. The DAT ship can be operated running ahead mode and astern mode in open water and ice conditions.